A forest of Signs : Art in the Crisis of Representation - Goldstein, Ann; Jacob, Mary Jane (Cambridge : the MIT press, 1989)
Baim, Richard ; Barry, Judith ; Beckman, Ericka ; Bender, Gretchen ; Birnbaum, Dara ; Bloom, Barbara ; Brauntuch, Troy ; Charlesworth, Sarah ; Goldstein, Jack ; Holzer, Jenny ; Johnson, Larry ; Jones, Ronald ; Kelley, Mike ; Koons, Jeff ; Kruger, Barbara ; Lawler, Louise ; Lawson, Thomas ; Levine, Sherrie ; Longo, Robert ; McCollum, Allan ; Mullican, Matt ; Nagy, Peter ; Prina, Stephen ; Prince, Richard ; Sherman, Cindy ; Simmons, Laurie ; Steinbach, Haim ; Syrop, Mitchell ; Welling, James ; Williams, Christopher
A forest of Signs : Art in the Crisis of Representation, The Museum of Contemporary Art, Los Angeles, May 7 - August 13, 1989
boek